Isolation and identification of bacterial contamination of raw meat in Thi-Qar province - Basim Jarullah (University of Thi-Qar Journal of Science, 2019)
Meat considers a favorite environment for bacterial growth due to rich composition with protein, fats, minerals,vitamins and other essential materials requirements for microorganism growth. Study concluded isolation and bacterialaccount of meat in Thiqar city markets. Study extends from November2014- March 2015. Thirty samples of meat (10from beef meat, 10 from sheep and 10 from poultry meat). Bacterial account shown that the highest contamination ofmeat samples found in sheep meat 16*106CUF/g (more than standard parameters of healthy suitable meat for humanconsumption) while the lowest bacterial account found in poultry meat 93*102CUF/g. Isolation and identification ofbacteria by morphological, differential media, biochemical tests and Gram stain results showed that prodomenet bacteriawere E.coli, Klebseilla, Staphylococcus aureas, Shegilla, Salmonella spp., Bacillus cereus, Enterobacter, Proteus,Micrococcus, Pseudomonas spp. and streptococcus spp. The predominant bacteria was E. coli about 35% in all samples,Followed by staphylococcus spp. 25%. Salmonella spp.1.2% isolated only from chicken meat samples.